Shallow Crustal Response to Arabia‐Eurasia Convergence in Northwestern Iran: Constraints From Multifrequency P‐Wave Receiver Functions. Issue 9 (19th September 2022) - Wang, Xu; Chen, Ling; Talebian, Morteza; Ai, Yinshuang; Jiang, Mingming; Yao, Huajian; He, Yumei; Ghods, Abdolreza; Sobouti, Farhad; Wan, Bo; Chu, Yang; Hou, Guangbing; et al.
Abstract: The Neo‐Tethys subduction and subsequent Arabia‐Eurasia continental collision invoked widespread Cenozoic tectono‐magmatism throughout the Iranian Plateau. We herein develop a new method to image the shallow crustal S‐wave velocity ( V s ) structure by joint inversion of multifrequency waveforms and horizontal‐to‐vertical ratios around the direct P phase in P‐wave receiver functions. Synthetic tests demonstrate the validity of our method in constraining the absolute V s values beneath single stations down to ∼12‐km depth. By applying this method to a seismic array of 63 stations with an average spacing of ∼10 km along the main profile, we construct a detailed shallow crustal V s model across the northwestern Iranian Plateau. The model is characterized by distinct high‐ and low‐velocity anomalies beneath the Iranian hinterland and the Zagros foreland fold‐and‐thrust belt, respectively. In combination with geological observations and laboratory data, the imaged high‐velocity anomalies (with V s of 3.2–3.9 km/s) may denote arc to intraplate magmatism beneath Central Iran and Alborz to the north, whereas the low‐velocity anomalies (with V s of ∼1.65 km/s) probably represent the marl/shale layers in Late Cretaceous and Paleocene beneath Zagros. The magmatic rocks at the Iranian hinterland exhibit strong variations in absolute V s, reflecting different bulk compositions with more mafic inland. The shale/marl layers could have acted as décollements to accommodate crustal deformation. Our observations underline both the key role of lithology‐controlled layering in sedimentary deformation at the Zagros fold‐and‐thrust belt and the change in compositions and forming‐environments of magmatic rocks at the Iranian hinterland. Plain Language Summary: Accurate velocity models of the shallow crust, especially in plate convergence zones, provide constraints on tectonic deformation and related mechanisms at shallow depths. However, existing seismic methods for imaging shallow crustal structures usually require dense and uniform ray‐path coverage, leading to limited application in areas with irregular distribution of stations and/or events. In this study, we propose inverting for shallow crustal velocity structures beneath single stations by using multifrequency signals around the direct P phase in receiver functions. The method is suitable for both the single‐station case and tectonically inactive regions. We applied the method to construct a detailed shallow crustal velocity model in northwestern Iran. The new model provides a more detailed view of the shallow crustal features of this tectonically complex region and helps to elucidate the Cenozoic tectono‐magmatic activities related to the Neo‐Tethys subduction and subsequent continental collision. Key Points: Frequency‐dependent signals around the direct P phase in receiver functions enable a better recovery of shallow crustal V s structures The inland change in compositions of magmatic rocks may reflect a shift from continent arc to intraplate magmatism in northwestern Iran The lithology‐controlled layering plays a key role in sedimentary deformation at the Zagros fold‐and‐thrust belt